2019
DOI: 10.1523/jneurosci.1511-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Visual Stimulation Induces a Neuroimmune Signaling Profile Distinct from Acute Neuroinflammation

Abstract: Many neurodegenerative and neurological diseases are rooted in dysfunction of the neuroimmune system; therefore, manipulating this system has strong therapeutic potential. Prior work has shown that exposing mice to flickering lights at 40 Hz drives gamma frequency (ϳ40 Hz) neural activity and recruits microglia, the primary immune cells of the brain, revealing a novel method to manipulate the neuroimmune system. However, the biochemical signaling mechanisms between 40 Hz neural activity and immune recruitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 66 publications
5
87
0
Order By: Relevance
“…33,34,35 Many studies showed that inhibition of IL-6 is a promising way to the treatment of in ammatory diseases. 36,37,38 We observed that HAND2-AS1 can regulate IL-6 in OA patients, which may be an upstream inhibitor of IL-6. However, this regulation could not be observed in controls groups, suggest that the inhibition of IL-6 by HAND2-AS1 is likely indirect and there may exist pathological mediators between HAND2-AS1 and IL-6.…”
mentioning
confidence: 73%
“…33,34,35 Many studies showed that inhibition of IL-6 is a promising way to the treatment of in ammatory diseases. 36,37,38 We observed that HAND2-AS1 can regulate IL-6 in OA patients, which may be an upstream inhibitor of IL-6. However, this regulation could not be observed in controls groups, suggest that the inhibition of IL-6 by HAND2-AS1 is likely indirect and there may exist pathological mediators between HAND2-AS1 and IL-6.…”
mentioning
confidence: 73%
“…IL-6 is a proinflammatory cytokine and has been proved participate in many inflammatory diseases [ 33 – 35 ]. Many studies showed that inhibition of IL-6 is a promising way to the treatment of inflammatory diseases [ 36 38 ]. We observed that HAND2-AS1 can regulate IL-6 in OA patients, which may be an upstream inhibitor of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term (>6 weeks) daily exposure to 40 Hz flickering lights decreased microglia-mediated inflammation in P301S and CK-p25 mice, improved behavioral performance, and reduced loss of neurons in various parts of the brain (59,120). This was confirmed by Garza et al (121), who found that 40 Hz flickering light administered to healthy mice increased the expression of cytokines, which plays a central role in microglial recruitment. In a healthy brain, microglia exercise a protective function that restrains the accumulation of Aβ and may prevent neurodegeneration (122).…”
Section: Intermittent Light At 40 Hz For Gamma Power Entrainmentmentioning
confidence: 58%